Project Management Spreadsheet Gaming Application - LEE, Wee Leong (Institutional Knowledge at Singapore Management University, 2011)
This chapter seeks to illustrate how simple spreadsheets can be used creatively with amazing outcomes. This will be demonstrated through a project management game, built entirely using standard spreadsheet features and functions. The project management game is designed as a teaching tool to allow players to experience project management in an interactive and fun atmosphere. In the game, players learn to respond to unforeseen events, make appropriate decisions to resolve issues, keep the project team motivated, and take corrective measures to keep the project on track and on target. This chapter is aimed at providing an overview of the game, discussing how it should be played, and explaining the underlying principles behind the rules of the game. It is not meant to be technical, although some amount of logical relationship between variables and mathematical functions will be discussed.